2021
DOI: 10.21203/rs.3.rs-154445/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Groundwater Quality Evaluation for Irrigation Suitable Using Geostatistical Algorithms

Abstract: The groundwater is the primary source for irrigation and other purposes in the Gaza Strip. The low irrigational water quality effects on the soil quality, which interrupts the growth of plants impacting agricultural yield and can cause risk to human health. Thus, it is essential to evaluate the water quality for irrigation uses. Therefore, it is a need to understand irrigation water quality better. This study mainly focuses on the assessment of the suitability of water for irrigation. Water quality indices, kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…For instance, Supriyanto and others' (2022) study in Polinella, India found that the groundwater quality in the area was mostly suitable for irrigation, but there were some limitations due to high levels of salinity and alkalinity in certain areas. The study in Gaza strip found that the groundwater in the area was contaminated with nitrate and other pollutants from agricultural activities and sewage (Gharbia et al, 2021). Likewise, Al-Hadith and others (2019) study in Baghdad, Iraq found that the groundwater in the area was contaminated with nitrate and other pollutants from agricultural and industrial sources.…”
Section: Salinity Hazardmentioning
confidence: 93%
“…For instance, Supriyanto and others' (2022) study in Polinella, India found that the groundwater quality in the area was mostly suitable for irrigation, but there were some limitations due to high levels of salinity and alkalinity in certain areas. The study in Gaza strip found that the groundwater in the area was contaminated with nitrate and other pollutants from agricultural activities and sewage (Gharbia et al, 2021). Likewise, Al-Hadith and others (2019) study in Baghdad, Iraq found that the groundwater in the area was contaminated with nitrate and other pollutants from agricultural and industrial sources.…”
Section: Salinity Hazardmentioning
confidence: 93%